(682) Classical Transportation Problem and Its Application in Iron-Ore Industry (UAR) مشكلة النقل الكلاسيكية وتطبيقها في صناعة خام الحديد - Boctor, Adel Louis; Amer, Roshdi (معهد التخطيط القومى, 2024)
This study addresses the classical transportation problem, offering a comprehensive overview and solutions. Chapter 1 introduces the topic, explores network representation, basic transportation theory, and solution methods, and highlights challenges such as degeneracy and programming complexities. Chapter 2 focuses on developing a computer program using Fortran, including flowchart diagrams and practical examples. Chapter 3 applies the methodology to an iron-ore problem, discussing decision types, engineering economics, and mathematical modeling. Chapter 4 presents numerical data and the final solution for the iron-ore problem. This work bridges theoretical principles with practical applications, emphasizing efficiency and problem-solving techniques.